Narrow Gap in Self-Efficacy Indicates Persistent Challenges in Women’s Uptake of Early Cervical Cancer Detection - Hidayah, Muziati; Azlina, Fitri Ayatul; Rahmah, Mutia (FORIKES, 2026)
Cervical cancer remains a major cause of mortality among women, particularly in developing countries such as Indonesia. Despite the high incidence, the coverage of early detection or screening is still low. One contributing factor is women’s lack of confidence (self-efficacy) in undergoing early detection procedures. This study aimed to identify the level of women’s self-efficacy in performing early detection of cervical cancer. This study employed a descriptive design with analysis presented in the form of frequencies and proportions. A total of 115 women of reproductive age were selected using consecutive sampling. Data were collected using a structured questionnaire and analyzed using descriptive analysis, including frequency distribution and proportion. The findings showed that 53.9% of respondents had high self-efficacy, while 46.1% had low self-efficacy in performing early detection of cervical cancer. Although the majority demonstrated high self-efficacy, the difference between the two categories was relatively small, indicating that self-efficacy remains a concern. In conclusion, most women exhibited high self-efficacy in undertaking early detection of cervical cancer; however, the narrow gap with those having low self-efficacy suggests the need for further improvement. Strengthening support from healthcare providers is essential to enhance women’s confidence and increase early detection coverage.Keywords: cervical cancer; early detection; self-efficacy